Pathological analysis and etiological assessment of pulmonary lesions and its association with pleurisy in slaughtered pigs - Arruda, Laíza Pinto [UNESP]; Malcher, Clarisse [UNESP]; Petri, Fernando Antônio Moreira [UNESP]; da Silva, Daniela Gomes [UNESP]; Storino, Gabriel Yuri [UNESP]; Almeida, Henrique Meiroz de Souza [UNESP]; Sonalio, Karina [UNESP]; Toledo, Leonardo Teófilo; de Oliveira, Luís Guilherme [UNESP] (Elsevier, 2024)
The intensification of pig farming has posed significant challenges in managing and preventing sanitary problems, particularly diseases of the respiratory complex. Monitoring at slaughter is an important control tool and cannot be overstated. Hence, this study aimed at characterizing both macroscopical and microscopical lesions and identifying the Actinobacillus pleuropneumoniae (APP), Mycoplasma hyopneumoniae (Mhyo), and Pasteurella multocida (PM) associated with pleurisy in swine. For this, a selected slaughterhouse in São Paulo State underwent a thorough examination of carcasses on the slaughter line, followed by lung sampling. The carcasses and lungs underwent macroscopical examination and were classified according to the score of pleurisy and lung samples were allocated into five groups, being: G0: score 0 – no lesions; G1: score 1; G2: score 2; G3: score 3; and G4: score 4. In total, 217 lung fragments were collected, for the histopathological evaluation and detection of the following respiratory pathogens: APP, Mhyo, and PM by qPCR. The results demonstrated that Mhyo and APP were the most prevalent etiological agents (single and co-identification) in lung samples, in different scores of pleurisies, while bronchopneumonia and bronchus-associated lymphoid tissue (BALT) hyperplasia lesions were the most frequent histopathological findings. Positive correlations were found between the quantification of APP DNA with 1) the score of pleurisy (R=0.254); 2) with the score of lung consolidation in all lung lobes (R=0.181 to R=0.329); and 3) with the score of lung consolidation in the entire lung (R=0.389). The study brings relevant information regarding the main bacterial pathogens associated with pleurisy in pigs and helps with understanding the relationship between the abovementioned pathogens and their impact on the respiratory health of pigs.
Keywords: BALT; Mycoplasma hyopneumoniae; Pigs; Pleuritis; Respiratory diseases